Strict implementation of the right to health as a fundamental right: ensuring universal access and equity in India - R. Kumar (Law and Safety)
This article explores the significance of recognizing the right to health as a fundamental right in India. It delves into the importance of ensuring universal access to healthcare services and promoting equity in health outcomes. By examining the current healthcare landscape in India, including existing challenges and disparities, this article argues for the urgent need to assert the right to health as a fundamental pillar of the country’s legal framework. It discusses the potential benefits of such recognition, including improved healthcare delivery, enhanced public health outcomes, and the fulfilment of basic human rights. Additionally, the article addresses potential policy implications and recommendations for policymakers to prioritize health equity and accessibility for all citizens. This article examines the constitutional underpinnings of the right to health in India, emphasizing its status as a fundamental right enshrined within Article 21 of the Indian Constitution and its reinforcement through Directive Principles of State Policy (DPSP). By delving into the legal framework, the article highlights the imperative of ensuring universal access and equity in healthcare delivery systems. It argues that recognizing health as a fundamental right not only aligns with constitutional principles but also serves as a moral imperative for the state to uphold the dignity and well-being of its citizens. Exploring the imperative of recognizing the right to health as a fundamental right in India. This abstract highlights the pressing need for universal access to healthcare services and equitable health outcomes. It underscores the potential benefits of such recognition, including enhanced healthcare delivery and the fulfilment of basic human rights, while also addressing policy implications for promoting health equity nationwide. The right to health was affirmed as a fundamental human right declared by the UN General Assembly in the 1948 UDHR (Article 25), emphasizing access to an adequate standard of living, including medical care.